1995
DOI: 10.1002/1520-6807(199504)32:2<114::aid-pits2310320207>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

When to intervene in selective mutism: The multimodal treatment of a case of persistent selective mutism

Abstract: An identification and treatment model differentiating Transient from Persistent Selective Mutism is proposed. The model incorporates treatment recommendations for Persistent Selective Mutism and suggests that interventions are not usually warranted for Transient Selective Mutism. The case study of a 6-year-old female manifesting Persistent Selective Mutism is presented. A multimodal treatment approach combining behavioral techniques with play therapy and family involvement was applied to improve her verbal int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Moldan (2005) developed a multimodal treatment that includes stimulus fading, play therapy, parent training, and a socialization group based on her conceptualization that SM results from a child's ‘attempt to self‐regulate internal anxiety and other emotional states’ (p. 292). Powell and Dalley (1995) used a variety of behavioral techniques (contingency management, shaping, self‐modeling, stimulus fading) in addition to ongoing play therapy sessions with the school psychologist to treat a six‐year‐old girl with persistent SM. After six months of treatment and at six‐month follow‐up the child was speaking in school in a manner consistent with her peers.…”
Section: The Present Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Moldan (2005) developed a multimodal treatment that includes stimulus fading, play therapy, parent training, and a socialization group based on her conceptualization that SM results from a child's ‘attempt to self‐regulate internal anxiety and other emotional states’ (p. 292). Powell and Dalley (1995) used a variety of behavioral techniques (contingency management, shaping, self‐modeling, stimulus fading) in addition to ongoing play therapy sessions with the school psychologist to treat a six‐year‐old girl with persistent SM. After six months of treatment and at six‐month follow‐up the child was speaking in school in a manner consistent with her peers.…”
Section: The Present Reviewmentioning
confidence: 99%
“…(1998) cautioned that several SM children in their study were unwilling to record an audiotape. In some cases listening to edited audiotapes actually increases the child's anxiety about speaking, making this intervention unsuitable for a certain segment of the SM population (Powell & Dalley, 1995). Since self‐modeling has often been combined with other behavioral techniques like positive reinforcement and stimulus fading, the extent to which it can be considered a stand‐alone intervention remains unknown.…”
Section: The Present Reviewmentioning
confidence: 99%
“…The concern expressed by Lumb and Wolff (1988) was that most studies did not give a justification for interventions, but were merely implemented because the child's behaviour was difficult to understand and was frustrating adults. As Powell and Dalley (1995) point out, one needs to balance the impact of the non-speaking behaviour with the child's overall development, such as factors like social adjustment and the inability to interact fully in various aspects of home or school. Gravell and France (1991) found that it is extremely rare for children above the age of 10 years to be identified as having selective mutism.…”
Section: Should We Intervene?mentioning
confidence: 99%
“…Moldan (2005) developed a multimodal treatment that includes stimulus fading, play therapy, parent training, and a socialisation group based on her conceptualisation that SM results from a child's 'attempt to self-regulate internal anxiety and other emotional states ' (p. 292). Powell and Dalley (1995) used a variety of behavioural techniques (contingency management, shaping, self-modelling, and stimulus fading) in addition to ongoing play therapy sessions with the school psychologist to treat a six-year-old girl with persistent SM. Jackson, Allen, Boothe, Nava, and Coates (2005) used a combination of systematic desensitisation, shaping, relaxation training, parent journaling, and play therapy to treat a six-year-old boy with SM.…”
Section: Introductionmentioning
confidence: 99%